Penggunaan Alkohol untuk Kepentingan Medis Tinjauan Istihsan - Muhammad Al Zuhri; Fery Dona (Journal of Law, Society, and Islamic Civilization, 2021)
This research discusses analytical studies regarding the use of alkohol in the medical world, in which alkohol in the Qur'an is haram. However, this thesis describes using the istihsan method which can change the law of origin from alkohol if it is used in the medical world, such as disinfectants and as a washing machine for medical devices. The purpose of this research is to examine the method of istihsan which can change the law of origin of alkohol.The research method used in this research is literary qualitative which requires a lot of library data. This is where the study in this study discusses the use of alkohol in the medical world. So the source of this research is able to present an analysis of the use of alkohol for medical purposes using the istihsan method.The results of research on the use of alkohol for medical purposes istihsan review. Alkohol is used in medical use only outside the body, as a disinfectant and also as a detergent for medical devices and as an external wound wash.